Intercropping with Achyranthes bidentata alleviates Rehmannia glutinosa consecutive monoculture problem by reestablishing rhizosphere microenvironment - Liu, Yazhou; Liu, Ye; Zeng, Chunli; Wang, Juanying; Nyimbo, Witness Joseph; Jiao, Yanyang; Wu, Linkun; Chen, Ting; Fang, Changxun; Lin, Wenxiong (Frontiers in Plant Science, 2022)
The consecutive monoculture of Rehmannia glutinosa leads to a serious decrease in its production and quality. Previous studies have demonstrated that intercropping altered species diversity and rhizosphere microbial diversity. However, it remained unknown whether the impaired growth of monocultured plants could be restored by enhanced belowground interspecific interactions. In the present research, a continuous cropping facilitator Achyranthes bidentata was intercropped with R. glutinosa under pot conditions, and three different types of root barrier treatments were set, including that complete belowground interaction (N), partial belowground interaction (S), and no belowground interspecies interaction (M), with the aims to investigate belowground interaction and the underlying mechanism of alleviated replanting disease of R. glutinosa by intercropping with A. bidentata. The results showed that the land equivalent ratio (LER) of the two years was 1.17, and the system productivity index (SPI) increased by 16.92 % under S treatment, whereas no significant difference was found in N and M regimes. In the rhizosphere soil, intercropping systems had significantly increased the contents of sugars and malic acid in the soil of R. glutinosa, together with the content of organic matter and the invertase and urease activities. Meanwhile, intercropping increased the community diversity of fungi and bacteria, and the relative abundance of potential beneficial bacteria, such as Bacillus, Nitrospira, and Sphingomonas, despite the pathogenic Fusarium oxysporum was still the dominant genus in the rhizospheric soil of R. glutinosa under various treatments. The results of antagonism experiments and exogenous addition of specific bacteria showed that Bacillus spp. isolated from rhizosphere soil had a significant antagonistic effect on the pathogen of R. glutinosa. Taken together, our study indicated that the R. glutinosa//A. bidentata intercropping systems alleviate the consecutive monoculture problem of R. glutinosa by recruiting beneficial bacteria. The studies we have conducted have a positive effect on sustainable agricultural development.